Vitamin E on performance, carcass characteristics and quality of pig’s cooked ham - Souza, Vera Lúcia Ferreira de; Silva, Rui Sérgio Ferreira da; Silva, Caio Abércio da; Gasparino, Eliane (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of vitamin E on performance, carcass characteristics and cooked ham quality. Ninety-six pigs were submitted to the following treatments: control; 100, 200 and 400 mg of vitamin E per kg of diet; during 116 days before slaughter. After slaughter, pig carcasses were measured, chilled, deboned and ham sections were removed to produce the cooked ham. Samples of frozen and cooked ham were analysed in relation to vitamin E and thiobarbituric acid (TBARS) contents. Growth rate mean was 789.81 g per day, feed intake mean was 2,418 g per day and feed:gain ratio was 3.06. The carcass showed the following mean: 113.57 kg alive weight; 85.90 kg carcass weight; 75.62% carcass yield; 61.28 mm ham depth; 23.16 mm backfat thickness and 49.28% lean meat. The cooked ham samples with the best levels of vitamin E showed 0.61 to 1.19 mg kg-1 TBARS, against 1.77 to 3.91 mg kg-1 TBARS for the control. Levels of supplementation of 200 mg vitamin E per kg of diet reduce the oxidation levels up to 70% in cooked ham and decrease backfat thickness.